The Development of Contemporary Balinese Cuisine: Sago Based Ravioli With Smoked Bebek Betutu Filling - Fanesia Dapawole; Sandy Dwiputra Yubianto; Ni Ketut Veri Kusumaningrum (Politeknik Internasional Bali, 2026)
This study is motivated by the need to revitalize Indonesian traditional cuisine, particularly Balinese gastronomy, through contemporary culinary innovation that aligns with modern consumer preferences while promoting the utilization of local food resources. The objective of this research is to develop and evaluate a contemporary dish in the form of sago flour ravioli filled with smoked bebek betutu, as an innovative adaptation of traditional Balinese cuisine. This study employed a Research and Development (R&D) method adapted from the Sugiyono R&D model, which includes the stages of product planning, product development, limited trials, expert validation, revision, and product testing through sensory evaluation. The product was evaluated using organoleptic (hedonic) testing involving 30 semi-trained and trained panelists (16 males and 14 females). The assessment used a five-point hedonic scale covering five sensory attributes: taste, aroma, color, texture, and appearance. The results of the organoleptic evaluation showed a high level of consumer acceptance. Taste was the most preferred attribute, with 90% of panelists responding positively (47% “like” and 43% “strongly like”). Aroma also received 90% positive responses, while color and appearance each obtained 80% positive responses. Texture showed comparatively lower acceptance, with 40% “like,” 53% neutral, and 7% “dislike,” indicating the need for further formulation improvement, particularly related to the physicochemical characteristics of sago-based dough. The novelty of this study lies in the integration of three key elements: (1) the use of sago flour as a gluten-free local raw material for ravioli dough, (2) the incorporation of smoked bebek betutu as a distinctive Balinese filling, and (3) the fusion of traditional Balinese culinary heritage with Italian pasta into a contemporary gastronomic product. This research demonstrates that local ingredients can be transformed into modern culinary innovations with strong sensory acceptance, supporting both culinary diversification and the preservation of Indonesia’s gastronomic heritage.